Project Cyclops - Hoover, Thomas, 1941- (Salt Lake City, UT : Project Gutenberg, 2010)
"Project Cyclops" by Thomas Hoover is a techno-thriller novel written in the early 1990s. The story revolves around Michael Vance, an ex-agent turned sailor, who finds himself embroiled in a high-stakes conflict involving Arab terrorists, a stolen thermonuclear warhead, and a cutting-edge laser launch facility in the Aegean Sea. As the terrorists take control of the facility, Vance becomes the unlikely hero, risking everything to thwart their plans and save countless lives. The opening of the book introduces us to Michael Vance as he navigates his handmade replica of Ulysses' ship, "Odyssey II", across the tumultuous Aegean waters. While he battles a brewing storm, the plot quickly escalates with the sudden attack from a Russian gunship piloted by Arab terrorists, who aim to seize a powerful laser facility guarding a nuclear warhead. As Vance's ship is destroyed in the ongoing chaos, he washes ashore, emerging as America's last hope against the terrorists. The tension builds as the multiple storylines of Vance's personal quest and the terrorists' sinister agenda collide, setting the stage for an intense narrative filled with action and suspense. (This is an automatically generated summary.)
Release date is 2010-11-14
Produced by Al Haines
Keywords: Suspense fiction; Nuclear warfare -- Fiction; Laser weapons -- Fiction; Aegean Sea -- Fiction